Empowerment as the key to health-enhancing physical activity in patients with rheumatoid arthritis and low physical function—a cross-sectional study - Andersson, M. L.E. ; 0000-0002-0217-5029; Wibring, K.; Bergman, S.; Bremander, A. (Clinical Rheumatology, 2025)
Objective: To study factors associated with health-enhancing physical activity in people with rheumatoid arthritis (RA), stratified by physical function. Method: In 2017, a survey was sent to 1543 patients with RA in the BARFOT (Better Anti-Rheumatic Pharmacotherapy) cohort, and 69% of patients responded. The survey included questions on physical function, pain, fatigue, self-reported disease activity, physical activity level, health-related quality of life, empowerment, comorbidities, and antirheumatic treatment. The patients were stratified based on physical function according to the Health Assessment Questionnaire (median value as cut off) into groups with worse vs. better physical function and further dichotomized to whether or not they met the World Health Organisation recommended level of health-enhancing physical activity (≥ 150 min/week). The Mann–Whitney U test or chi-squared test was used to analyse group differences. A logistic regression model adjusted for age and sex was used to study factors associated with health-enhancing physical activity. Results: In total, 1047 patients had available data on physical function, mean age 67 years (SD 13), 72% women. Younger age, non-obesity, less pain, less fatigue, and lower disease activity were associated with health-enhancing physical activity, irrespective of physical function level. In the group with worse physical function, better health-related quality of life and empowerment were also associated with health-enhancing physical activity. Conclusion: The results indicate a complex relationship between various factors that can affect the level of physical activity in individuals with RA. Strengthening empowerment could be a key when supporting improvement in physical activity in patients with RA with impaired physical function. (Table presented.)
Publisher Copyright: © The Author(s) 2025.
Keywords: Empowerment; Physical activity; Physical function; Rheumatoid arthritis